From Legacy to Memory: Reckoning with Racial Violence at the National Memorial for Peace and Justice. (March 2021) - Simko, Christina
How are the legacies of violent pasts brought into collective memory? Even as social scientists have systematically documented the long shadow that racially motivated lynching has cast into the present, this history has had little place within dominant national narratives. Recently, however, the Equal Justice Initiative's National Memorial for Peace and Justice in Montgomery, Alabama, has broken through the silence, attracting widespread attention and praise. This article examines how the memorial creatively adapts morally and emotionally resonant themes from dominant national narratives to bridge long-standing mnemonic cleavages between Black and white Americans. In addition, the article provides preliminary evidence that the legacies of racial violence are gaining a place in national memory.